2017
DOI: 10.1039/c7ay02275a
|View full text |Cite
|
Sign up to set email alerts
|

Combined headspace single-drop microextraction and solid-phase microextraction for the determination of phenols as their methyl ethers by gas chromatography-mass spectrometry

Abstract: A combination of headspace large volume single drop extraction and solid phase microextraction permitted attainment of high sensitivity by transferring an overall large mass of analytes into a gas chromatograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The faster equilibration time was likely because the water matrix was absorbed onto the polar TLC silica coating (increasing the concentration and vapor pressure of the nonpolar IBMP) and because the silica gel had a high surface area (allowing for more rapid volatilization). At least one other study has reported similar improvements in HS-SPME equilibration times using small volumes; Jain et al reported rapid (5 min) SPME extraction from a 7 μL solvent drop …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The faster equilibration time was likely because the water matrix was absorbed onto the polar TLC silica coating (increasing the concentration and vapor pressure of the nonpolar IBMP) and because the silica gel had a high surface area (allowing for more rapid volatilization). At least one other study has reported similar improvements in HS-SPME equilibration times using small volumes; Jain et al reported rapid (5 min) SPME extraction from a 7 μL solvent drop …”
Section: Resultsmentioning
confidence: 89%
“…At least one other study has reported similar improvements in HS-SPME equilibration times using small volumes; Jain et al reported rapid (5 min) SPME extraction from a 7 μL solvent drop. 21 Analyte volatilization from TLC spots was so rapid that it necessitated the use of a multi-channel pipet to minimize signal loss from early spotted samples. To slow sample volatilization, we also evaluated the effects of adding surfactants to the sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Wine is a complex matrix formed by a mixture of volatile and non‐volatile compounds, most of which are present at low concentration; as a result, extraction and/or preconcentration steps are always required prior to the chromatographic quantification. Several extractive techniques have been applied to the extraction of phenols from red wines, from the old and widely used liquid–liquid extraction (LLE), usually requiring several laborious extraction steps and the use of large volumes of toxic organic solvents (Moio and Etievant ), to the more recent techniques, aiming at the reduction or even elimination of hazardous solvents, such as solid‐phase extraction (SPE) using conventional sorbents (Allen et al ) or molecular‐imprinted polymers (Garcia et al ), stir bar sorptive extraction (SBSE) (Diez et al ), single drop microextraction (SDME) (Jain et al ), direct immersion solid‐phase microextraction (DI‐SPME) (Barnaba et al ), headspace solid‐phase microextraction (HS‐SPME) (Monje et al , Carrillo and Tena ), quick easy cheap effective rugged safe (QuEChERS) (Valente et al ) and dispersive liquid–liquid microextraction (DLLME) (Fariña et al , Pizarro et al , Carpinteiro et al ). Overall, microextraction techniques present limits of quantification and of detection lower than SPE and LLE with the benefit of requiring a lower sample volume and being easy to perform and to automate.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity merit of programmed temperature vapourisation in GC was simulated by augmented extraction in a bigger drop (10 μL) in HS-SDME, and subsequent headspace transfer of analytes to SPME fiber for injection. 26 In another modification, nitrogen was bubbled upwards through the sample solution taken in a column placed with a 15 μL extraction drop of 1-undecanol in the headspace supported by a bell-shaped needle sleeve. 27 The nitrogen bubbling effectively transported analytes to the headspace, and a bigger than usual solvent drop contributed to higher and faster extraction.…”
Section: Introductionmentioning
confidence: 99%